Video game play and consciousness - Gackenbach, Jayne (My University, 2012)
A program of research into the effects of video game play on subsequent night-time dreams is reviewed. The chapter begins with a brief introduction to the value of dreams in terms of information processing and a discussion of why video game play is valuable for the study of dreams. Three areas of inquiry in terms of video game effects are then examined. These include cognitive dimensions of dreams such as lucid and control dreams, emotional dream elements such as nightmares, and the creative elements of dreams such as their bizarreness. In each case, video game play appears to have had an impact on these dream elements. Specifically, there is some indication of increased lucid dreaming, but also a strong finding of increased control in dreams. Additionally, nightmares may be less frightening for video game players. Finally, gamers’ dreams are more bizarre even when media exposure the day before the dream is controlled. These effects are explained as parallel to the effects from the practice of meditation on dreams. Both video game play and meditation require prolonged focused attention.
Keywords: Video games -- Psychological aspects